A Pilot Study using the Compensatory Reserve Index to evaluate individuals with Postural Orthostatic Tachycardia syndrome. (30th December 2020) - Shahi, Niti; Shirek, Gabrielle; Pickett, Kaci; Schwartz, Alexandra; Shoop, Jamie; Phillips, Ryan; Workman, Rachel; Kaplan, David; Pitula, Clio; Moulton, Steven
Abstract: Purpose: The diagnosis of Postural Orthostatic Tachycardia syndrome traditionally involves orthostatic vitals evaluation. The Compensatory Reserve Index is a non-invasive, FDA-cleared algorithm that analyses photoplethysmogram waveforms in real time to trend subtle waveform features associated with varying degrees of central volume loss, from normovolemia to decompensation. We hypothesised that patients who met physiologic criteria for Postural Orthostatic Tachycardia syndrome would have greater changes in Compensatory Reserve Index with orthostatic vitals. Methods: Orthostatic vitals and Compensatory Reserve Index values were assessed in individuals previously diagnosed with Postural Orthostatic Tachycardia syndrome and healthy controls aged 12–21 years. Adolescents were grouped for comparison based on whether they met heart rate criteria for Postural Orthostatic Tachycardia syndrome ( physiologic Postural Orthostatic Tachycardia syndrome ). Results: Sixty-one patients were included. Eighteen percent of patients with an existing Postural Orthostatic Tachycardia syndrome diagnosis met heart rate criteria, and these patients had significantly greater supine to standing change in Compensatory Reserve Index (0.67 vs. 0.51; p< 0.001). The optimal change in Compensatory Reserve Index for physiologic Postural Orthostatic Tachycardia syndrome was 0.60. Patients with physiologic Postural Orthostatic Tachycardia syndrome were more likely to report previous diagnoses of anxiety or depression (p = 0.054, 0.042). Conclusion: An accurate diagnosis of Postural Orthostatic Tachycardia syndrome may be confounded by related comorbidities. Only 18% (8/44) of previously diagnosed Postural Orthostatic Tachycardia syndrome patients met heart rate criteria. Findings support the utility of objective physiologic measures, such as the Compensatory Reserve Index, to more accurately identify patients with true autonomic dysfunction.